Probing a proactive home: Challenges in researching and designing everyday smart environments - Mäyrä, Frans; Soronen, Anne; Koskinen, Ilpo; Kuusela, Kristo; Mikkonen, Jussi; Vanhala, Jukka; Zakrzewski, Mari (Human Technology, 2006)
Based on the results of a 3-year interdisciplinary study, this article presents an approach in which proactive information technology was introduced into homes, and discusses the derived design principles from a human-centered perspective. The application of proactive computing in homes will face particularly sensitive conditions, as familiar and reliable household elements remain strongly preferred. Since there is considerable resistance towards the increase of information technology in homes, both the calm system behaviors and the degree of variety in aesthetic designs will play major roles in the acceptance of proactive technology. If proactive technology will be an embedded part of a home's structures and furniture, it needs to blend with the normal, cozy standards of a real living environment and aim to enhance the homeyness or the key social and aesthetic qualities of homes.